Pengungkapan Diri Gay dengan Teman Laki-laki Heteroseksual tentang Orientasi Seksual - Olivia Anjani; Wiwid Noor Rakhmad (Interaksi Online, 2019)
In the process of self-disclosure, gays experience the complexity to reveal or hide their sexual identities. Tension in expressing sexual orientation is often felt by gays in friendships between gays with heterosexual men. Researchers conducted this study with the intention to find out the limits of the criteria used as gay considerations in closing or revealing themselves. In addition, it is also to find out how to communicate used in the disclosure or concealment of sexual identity to heterosexual men. using descriptive qualitative research methods. Data collection method used was an interview, with a number of informants 5 gay men. The results showed: (1) The process of self-disclosure of gay people to heterosexual male friends goes through a fairly long stage starting from being able to identify themselves, disclosure to the other immediate environment and finally to heterosexual men. (2) The purpose in self-disclosure is to foster a sense of being understood, accepted and equalized by his male friends. (3) Found criteria for consideration in the form of culture, gender, context, motivation and risk-benefit